(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper discusses the essays by Isidora Sekulić from the point of view of gender studies. The first part explains the reasons for the essay being an ideal form of women’s participation in culture and why Isidora Sekulić often used it when referring to foreign and domestic female writers. What the genre under scrutiny allowed to its user was formal and thematic independence, strengthening the voice of a female author as well as the expression of her intellectual beliefs. The next part of the paper presents Isidora Sekulić’s essay written in 1911: Is Constantin Brunner right? and her polemic with the claims of German philosopher C. Brunner regarding the inferiority of woman’s mind. Finally, the paper presents Sekulić’s essays devoted to the European women writers, such as Virginia Woolf, Selma Lagerlőf and François Sagan, and Serbian female writers (Danica D. Hristić, Danica Marković, Jelena Dimitrijević, Jelisaveta Ibrovac, Milica Janković, Vida J. Radović, Smilja Đaković, Milica Kosić Selem). On this basis, Isidora Sekulić’s evolution from a universal to a strongly gender-oriented attitude is presented.